The Contribution of Declines in Blood Lead Levels to Reductions in Blood Pressure Levels: Longitudinal Evidence in the Strong Heart Family Study - Wil Lieberman‐Cribbin; Zheng Li; Michael Lewin; Patricia Ruiz; Jeffery M. Jarrett; Shelley A. Cole; Allison Kupsco; Marcia O'Leary; Gernot Pichler; Daichi Shimbo; Richard B. Devereux; Jason G. Umans; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Chronic lead exposure is associated with both subclinical and clinical cardiovascular disease. We evaluated whether declines in blood lead were associated with changes in systolic and diastolic blood pressure in adult American Indian participants from the SHFS (Strong Heart Family Study). Methods and Results Lead in whole blood was measured in 285 SHFS participants in 1997 to 1999 and 2006 to 2009. Blood pressure and measures of cardiac geometry and function were obtained in 2001 to 2003 and 2006 to 2009. We used generalized estimating equations to evaluate the association of declines in blood lead with changes in blood pressure; cardiac function and geometry measures were considered secondary. Mean blood lead was 2.04 μg/dL at baseline. After ≈10 years, mean decline in blood lead was 0.67 μg/dL. In fully adjusted models, the mean difference in systolic blood pressure comparing the highest to lowest tertile of decline (>0.91 versus <0.27 μg/dL) in blood lead was −7.08 mm Hg (95% CI, −13.16 to −1.00). A significant nonlinear association between declines in blood lead and declines in systolic blood pressure was detected, with significant linear associations where blood lead decline was 0.1 μg/dL or higher. Declines in blood lead were nonsignificantly associated with declines in diastolic blood pressure and significantly associated with declines in interventricular septum thickness. Conclusions Declines in blood lead levels in American Indian adults, even when small (0.1–1.0 μg/dL), were associated with reductions in systolic blood pressure. These findings suggest the need to further study the cardiovascular impacts of reducing lead exposures and the importance of lead exposure prevention.